Diagnostic Challenges in Adenomyoepithelioma of the Breast: A Rare Case Report - Zachariah Chowdhury (Journal of Clinical and Diagnostic Research, 2020)
ABSTRACT Adenomyoepithelioma (AME) is an uncommon tumour of breast, which is common in middle aged and older adults (>60 years). It is characterised by dual differentiation of cells into luminal as well as myoepithelial cells. Herein we report a case of a 22-year-old female who presented with a solitary swelling in the upper outer quadrant of the left breast, diagnosed as fibrocystic breast disease on Fine Needle Aspiration Cytology (FNAC). Excisional biopsy and histopathologic examination showed features suggestive of AME, which was confirmed on Immunohistochemistry (IHC) staining. On retrospective review of the cytology slides, a biphasic appearance was discerned; the myoepithelial cells probably having been masked by the cystic degeneration. AMEs are generally benign. However, in view of substantial reports of local recurrences, malignant transformations and metastases, accurate distinction of this lesion is crucial. Here, the authors report this rare case, to emphasise the importance of considering this entity in the differential diagnosis of a focal solid lesion in the breast, and to underline the accompanying diagnostic pitfalls.